2021
DOI: 10.1186/s12935-021-01999-5
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the Hippo pathway as a therapeutic target for combating endocrine-resistant breast cancer

Abstract: Drug resistance is always a great obstacle in any endocrine therapy of breast cancer. Although the combination of endocrine therapy and targeted therapy has been shown to significantly improve prognosis, refractory endocrine resistance is still common. Dysregulation of the Hippo pathway is often related to the occurrence and the development of many tumors. Targeted therapies of this pathway have played important roles in the study of triple negative breast cancer (TNBC). Targeting the Hippo pathway in combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 154 publications
(150 reference statements)
0
4
0
Order By: Relevance
“…ER signaling is the main driving force for the growth of ER + breast carcinomas ( 39 ). The noncanonical roles of the components of the Hippo pathway crucially impact ER signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ER signaling is the main driving force for the growth of ER + breast carcinomas ( 39 ). The noncanonical roles of the components of the Hippo pathway crucially impact ER signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The noncanonical roles of the components of the Hippo pathway crucially impact ER signaling. YAP1 and TEAD4, coregulators of ERα on enhancers, exhibit augmented binding to ERα upon estrogen stimulation and are required for the induction of target genes of ER signaling ( 39 , 40 ). SASH1 expression was significantly inversely correlated with nuclear ER expression ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, YAP1-mediated regulation of ferroptosis is starting to be discussed as one of the potential mechanistic links between chemoresistance and high YAP1 activity [49][50][51][52][53]. In addition, an increasing number of studies have shown that the Hippo pathway is closely linked to endocrine therapy resistance in breast and prostate cancer [54,55].…”
Section: Yap1 As a Mechanism Of Intrinsic And Acquired Drug Resistancementioning
confidence: 99%
“…Quite a few studies have revealed the critical function of Hippo signaling in TNBC progression [9][10][11][12]. The normal function of Hippo signaling is important in tissue regeneration, organ size control and cancer prevention [13].…”
Section: Introductionmentioning
confidence: 99%